Forensic Linguistic Study Of Experiential Meaning In Minutes Of Inheritance Lawsuit At The Medan District Court - Sipapaga, Desima; Setia, Eddy; zein, T. Thyrhaya (International Journal of Educational Research & Social Sciences, 2022)
In the case of language in the realm of law, lately it is often discussed in forensic linguistic studies. This study analyzes the minutes of inheritance lawsuits in the Medan District Court. The data used is an official report text that comes from an inheritance lawsuit at the Medan District Court. In this data, researchers formulate experiential meaning. The research method used is descriptive qualitative method using Forensic Systemic Linguistics (LSF) theory. And data analysis through four stages proposed by Miles, Huberman, and Saldana, namely data collection, data condensation, data presentation, and data verification. The results of this study on experiential meaning which has 6 processes, namely, material, mental, relational, behavioral, verbal and tangible. In these six processes, the most dominant is the verbal process as much as 32.3% in the minutes of inheritance lawsuits at the Medan District Court.